Description of two species in the alpheid shrimp genus Athanas Leach, 1814, with remarks on A. amazone Holthuis, 1951 (Decapoda, Caridea) - Anker, Arthur; Ahyong, Shane T. (Zootaxa, 2007)
Two new species of the alpheid genus Athanas Leach, 1814 are described and illustrated. Athanas sydneyensis n. sp., is described on the basis of several specimens collected near Sydney, New South Wales, Australia. This species is closely related to the polymorphic A. phyllocheles Banner & Banner, 1983 known only from La Réunion in the southwestern Indian Ocean. Athanas ivoiriensis n. sp., is described on the basis of a single specimen collected off Ivory Coast, West Africa. This species appears to be most closely related to A. amazone Holthuis, 1951 from the tropical eastern Atlantic and the Mediterranean Sea. The morphological variability of A. amazone and A. phyllocheles, including polymorphism of the chelipeds, are discussed.